Editor's Notes - Javier, Jem R. (The Archive; The Archive Classics: Legends of the Atayal People on Formosa, 2023)
This issue of The Archive Classics features a bilingual edition of Otto Johns Scheerer’s paper titled “Sagen der Atayalen auf Formosa” [Legends of the Atayal people on Formosa], originally published by Dietrich Reimer Hamburg Boysen in its 1932 issue of Zeitschrift für Eingeborenen-Sprachen .